2019
DOI: 10.1136/bmjopen-2018-028284
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Smoking Habits Investigation based on Physiology and Context (ASSIST) using wearable sensors and mobile phones: protocol for an observational study

Abstract: IntroductionSmoking prevalence continues to be high over the world and smoking-induced diseases impose a heavy burden on the medical care system. As believed by many researchers, a promising way to promote healthcare and well-being at low cost for the large vulnerable smoking population is through eHealth solutions by providing self-help information about smoking cessation. But in the absence of first-hand knowledge about smoking habits in daily life settings, systems built on these methods often fail to deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This was an observational study of smoking behavior in a real-life setting, following the protocol reported in [ 19 ]. Smoker volunteers were recruited from the Flanders area of Belgium to participate in a 4-week experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an observational study of smoking behavior in a real-life setting, following the protocol reported in [ 19 ]. Smoker volunteers were recruited from the Flanders area of Belgium to participate in a 4-week experiment.…”
Section: Methodsmentioning
confidence: 99%
“…When the experiment began, the participants downloaded and installed an experimental app called ASSIST [ 19 ] on their smartphone. Next, they were given 2 wearable sensors, 1 electrical lighter, and instructions on the use of these sensors and the app.…”
Section: Methodsmentioning
confidence: 99%